Production and characterization of biodiesel fuel produced from third-generation feedstock - Verma, Suraj; Sahu, Deepak; Almutairi, Bader O. (Frontiers in Materials, 2024)
Biodiesel is an eco-friendly, renewable alternative fuel, and it can be obtained from soybean oil, vegetable oils, animal fat, or microalgae. This study presents a comprehensive investigation into the production and characterization of microalgae biodiesel utilizing multiple analytical techniques, including CHNSO analysis, Fourier-transform infrared spectroscopy (FTIR), gas chromatography–mass spectrometry (GC–MS), and proton nuclear magnetic resonance spectroscopy (1H NMR). The CHNSO analysis revealed the elemental composition of biodiesel blends, highlighting the effects of TiO2 nanoparticle concentrations on carbon, nitrogen, sulfur, and oxygen content. With increasing TiO2 concentration, a steady increase in the carbon content and a gradual decrease in the nitrogen content were observed. According to the CHNSO analysis, the sulfur content of blended biodiesel was found to be lower than that of fossil diesel, with an empirical formula of CH2.26N0.000584S0.000993O0.0517. FTIR and 1H NMR spectroscopy confirmed the synthesis of biodiesel. Fourier-transform infrared resonance confirmed the presence of ester groups at 1732 cm-1, and a prominent peak at 1,455 cm-1 indicated a higher carbon content in the blended biodiesel. GC–MS analysis identified compounds of fatty acid methyl esters (FAMEs) and hydrocarbons. The major components of FAMEs were 9-octadecenoic acid methyl ester (C19H36O2), linoleic acid ethyl ester (C20H36O2), and hexadecanoic acid methyl ester (C17H34O2), with compositions 20.65%, 9.67%, and 6.26%, respectively. The presence of methyl ester in the blended fuel suggests its potential as an alternative fuel source.